2007
DOI: 10.1110/ps.062448907
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic stability of a cold‐adapted protein, type III antifreeze protein, and energetic contribution of salt bridges

Abstract: A thermodynamic analysis of a cold-adapted protein, type III anti-freeze protein (AFP), was carried out. The results indicate that the folding equilibrium of type III AFP is a reversible, unimolecular, two-state process with no populated intermediates. Compared to most mesophilic proteins whose folding is twostate, the psychrophilic type III AFP has a much lower thermodynamic stability at 25°C, ;3 kcal/mol, and presents a remarkably downshifted stability-temperature curve, reaching a maximum of 5 kcal/mol arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 78 publications
6
29
1
Order By: Relevance
“…In spite of this, the spectrum of type III AFP shows a native-absorption band between 215 and 230 nm, and it allows us to conduct unfolding experiments. It is important to note that the far UV-CD spectrum results are similar in shape to that obtained by other groups in the presence of salt [17,19]. …”
Section: Resultssupporting
confidence: 83%
“…In spite of this, the spectrum of type III AFP shows a native-absorption band between 215 and 230 nm, and it allows us to conduct unfolding experiments. It is important to note that the far UV-CD spectrum results are similar in shape to that obtained by other groups in the presence of salt [17,19]. …”
Section: Resultssupporting
confidence: 83%
“…By extrapolating the k 2 values obtained at [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] C to the T m at 28.5 C (R 2 5 0.981, exponential regression) we obtain a k 2 and k 1 of 0.00526 min…”
Section: Low Melting Temperature Of Rmafp1mentioning
confidence: 99%
“…A high refolding capacity has also been observed for other AFPs. 13,[19][20][21][22] In two cases the activity of the protein was measured to ensure that the protein refolded to its native state, and only one of these showed that the protein (DAFP-4) had retained most of its activity. Here, we also show that the RmAFP1 has activity almost similar to the untreated control after subjection to 10 heat cycles to both 60 and 70 C. When the protein sample was repeatedly heated to 80 C the DH unfold decreased by 6.5% of the initial value per run (Fig.…”
Section: Refolding Capabilities and Refolding Rates Of Rmafp1mentioning
confidence: 99%
See 2 more Smart Citations